Management fundamentals : concepts, applications, skill development - Lussier, Robert N. (Cincinnati, OH : South-Western College, 2000)
This book is divided into five parts: Introduction; Planning skills; Organizing skills; Leading skills; and Controlling skills.
Keywords: Economics; Management; Management